High-definition ultrasonography in the evaluation of the reproductive tract of bitches during the follicular phase of the estrous cycle - Aires, Luiz Paulo Nogueira [UNESP]; Gasser, Beatriz [UNESP]; Silva, Priscila [UNESP]; Del Aguila Da Silva, Priscila [UNESP]; Silveira, Marcus Vinícius [UNESP]; Carneiro, Rafael Kretzer [UNESP]; IwaoYamada, Diego; Padilha-Nakaghi, Luciana Cristina [UNESP]; Uscategui, Ricardo Andrés Ramirez [UNESP]; Spada, Stefano; Russo, Marco; Feliciano, Marcus Antônio Rossi [UNESP] (Elsevier, 2021)
The aim was to sonographically evaluate the reproductive tract of bitches during the follicular phase of the estrous cycle using High Density (HD) ultrasonic techniques. Females (n = 8) were evaluated at five different times throughout the follicular phase, as determined by vaginal cytology and blood progesterone concentrations. Ultrasonic exams were performed using the ACUSON S2000/SIEMENS device utilizing a multifrequency HD transducer (5.5–18 MHz). Videos of the ovaries were obtained and recordings were evaluated using a DICOM viewer software for counting and measuring the ovarian structures, which were assigned to groups based on diameter in mm: G1: ≤ 1; G2: from 1.01 to 3.5; G3 from 3.51 to 5.5; G4: from 5.51 to 10. There was a greater uterine thickness with the progression of the follicular phase (P < 0.05). Six distinct regions were identified in the uterine wall. The ovarian dimensions increased (P < 0.05) as stage of the follicular phase advanced. There was fluid detected around the ovaries after ovulation. There was a characteristic fat tissue hyperechogenicity around the ovaries at all timepoints. There was a difference in the number of ovarian structures of each dimension group at each time there were assessments (P < 0.05). There was a difference in diameter of the largest ovarian structure and in average value of wall thickness at all timepoints when there were evaluations (P < 0.05). The HD ultrasonography technique provides for excellent image resolution, allowing for a more precise characterization of the bitch's reproductive structures and changes occurring during the follicular phase of the estrous cycle.
Keywords: Canine; Corpus luteum; Estrous cycle; High density; Ovarian follicle; Uterus